Polish-Ukrainian language contacts in the context of dialectal lexicography in the late 19th century: Słowniczek prowincyоnalizmów podolskich by A. Kremer - Horofianiuk, Inna (Przegląd Wschodnioeuropejski, 2026)
The article explores Polish-Ukrainian language contacts in the context of dialectal lexicography exemplified by Słowniczek prowincуоnalizmów Podolskich, ułozony w Kamieńcu Podolskim w roku 1863 (further in the article – Dictionary) by Aleksander Кrеmer, a Polish scholar who lived in Kamyanets-Podilsky, a city in the region of Podillia in Ukraine. In his Dictionary, Kremer documented the local dialect of the Polish language spoken by Polish- -speaking residents in Kamyanets-Podilsky, which contained lexical items borrowed from Ukrainian. Accordingly, Kremer’s Dictionary provides a rare insight into Polish-Ukrainian language contacts on the dialectal level. Furthermore, Kremer compared the dialectal lexical items collected and recorded by him in Kamyanets-Podilsky with the lexical material of Słownik języka polskiego compiled by S. Linde (1807-1814). However, Kremer’s Dictionary has not been properly researched in the prior studies. In this light, the aim of this article is to identify and systematize the Polish-Ukrainian language contacts that are reflected in Dictionary. The results of the study have revealed multiple instances of the local dialect of Ukrainian in Kremer’s Dictionary, which are further discussed in the article. The results of the study are relevant to historical linguists, dialectologists, and ethnographers in Ukraine as well as in Poland.